Rejuvenation solution as an adjunct cold storage solution maintains physiological haemoglobin oxygen affinity during early‐storage period of red blood cells. Issue 5 (12th March 2020) - Evans, Brooke A.; Ansari, Andrea K.; Srinivasan, Amudan J.; Kamyszek, Reed W.; Stoner, Keaton C.; Fuller, Matthew; Poisson, Jessica L.; Welsby, Ian J.
Abstract: Background: Red blood cell (RBC) units accumulate morphologic and metabolic lesions during storage before transfusion. Pyruvate–inosine–phosphate–adenine (PIPA) solutions (Rejuvesol, Biomet, Warsaw, IN) can be incubated with RBC units to mitigate storage lesions. This study proposes a PIPA treatment process, termed cold 'rejuvenation', using Rejuvesol as an adjunct additive solution, to prevent biomechanical storage lesions while avoiding the 1 h PIPA incubation required with standard PIPA treatment. We compared the efficacy of cold to standard 'rejuvenation' in improving metabolic lesions that occur during cold storage of RBCs, without altering function. Methods: Twelve leucoreduced, A‐positive RBC units were obtained. Each unit was aliquoted into either control (standard storage), washed (W), standard rejuvenation (SR) or cold rejuvenation (CR) groups, the latter two requiring washing. A volume‐adjusted dose of Rejuvesol was instilled into the CR group upon receipt (Day 3). After 15 days of storage, p50, RBC deformability, in‐bag haemolysis and mechanical fragility were analysed. 'Any treatment' is defined as W, SR and CR, with comparisons in reference to control. Results: Higher p50s were seen in rejuvenated groups (>30 mmHg vs. <19 mmHg; P < 0·0001). Any treatment significantly increased elongation index ( P = 0·034) but did not significantly increase in‐bag haemolysis ( P = 0·062). Mechanical fragility was not significantly different between groups ( P = 0·055) at baseline, but the control (CTL) group was more fragile after 2 h in a cardiac bypass simulation than any treatment ( P < 0·0001). Conclusions: This study demonstrates that rejuvenation (standard or cold) prevents the leftward p50 shift of storage lesions without detrimental effect on RBC deformity, in‐bag haemolysis or mechanical fragility.